2017
DOI: 10.5115/acb.2017.50.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Age-related trends of lesser pelvic architecture in females and males: a computed tomography pelvimetry study

Abstract: The pelvis and the spine form a system balancing human skeleton. Within this system, the pelvis adapts to age-related changes in the spine. Previous studies were predominantly focused on changes of pelvic parameters in the sagittal plane. The aim of this study was to reveal age-related changes of lesser pelvic dimensions at different levels of the pelvic cavity in the sagittal and coronal planes and to explore sexual dimorphism in age-related tendencies. The computed tomography pelvimetry was performed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The patients' mean age was 50.23 ± 14.36 years in this study. In a study by Kolesova et al, 2017, pelvic size difference was associated with changes in age. In their study, they observed age-related changes in pelvic cavity's linear parameters and verified a more horizontal sacrum location and sacral floor's anterior tilt in accordance to aging.…”
Section: Discussionmentioning
confidence: 93%
“…The patients' mean age was 50.23 ± 14.36 years in this study. In a study by Kolesova et al, 2017, pelvic size difference was associated with changes in age. In their study, they observed age-related changes in pelvic cavity's linear parameters and verified a more horizontal sacrum location and sacral floor's anterior tilt in accordance to aging.…”
Section: Discussionmentioning
confidence: 93%
“…Beyond those listed above, other factors can also have effects on these reliability ratings. In particular, anatomical changes of PFM due to age (such as increased looseness of the vaginal walls, smaller width of the labia minora, 6 increased distance between the ischial spines, 7 increased transverse 8 and sagittal 7 diameter of the vagina, decreased muscle mass, decreased area of muscle crosssection, and increased muscle collagen accumulation 9 ) and parity (which is associated with increased vaginal distensibility 9 ) may lead to a decrease in subjectsʼ capacity to produce force with the PFM and a decline in its function. 8,9 These changes may be associated with different contraction degrees responses during PFM assessment.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that there was no change in pelvic proportion to ischial height in female while the distance of transverse pelvic diameter shortens with age. 7 As it is stated previously, age-related ankylotic processes decreased sacroiliac joints motility and facilitated these changes. [8][9][10] There were signi cant differences (p < 0.05) on radiologic components measured between male and female except for transverse diameter of the sacral segment (p = 0.180).…”
Section: Discussionmentioning
confidence: 78%